Avaliação do funcionamento de um sistema de biorretenção através da fitorremediação para jardins de chuva em áreas urbanas - Cardoso, Sandra Magda Mattei (2021)
Biorretention is a kind of big bag to collect, store, filter and infiltrate the runoff of urban rainwater. This system became popular in many parts of the world, but until the end of this study so far has not been implemented in Brazil as a common practice. However, there are some prototypes installed in especific universities in Brazil, which can provide data from both qualitative and quantitative performance of that system. This research is abiorretention’s technique through of the phytoremediation to rain gardens in urban areas,it has used to minimize the negative effects caused by flood or so much water in the streets. This system is combined with some plants which can help reducing the pollution of heavy metals found in water, with an emphasis on efficiency of removing pollutants like: Cadmium (Cd), Lead (Pb), Copper (Cu), Iron (Fe), Fluoride (F), Mercury (Hg) and Zinc (Zn), this literature reviewis about: rain gardens, biorretention in urban areas and phytoremediation. The main objective of this work was do an analysis in the laboratory with the resolution of the CONAMA 357/05of the water quality, after that, the collected water goes through the prototype / bioretention´s system with phytoremediation using the plant species, AlocasiaMacrorhiza, popularly known in Brazil as Elephant Ear, this refered plant has an characteristic in the metal absoption. For that work, it is being proposed three analyzes in different periods of the year, first one in December /2020, the second one in March /2021 and a third in May /2021. The gatherring’s water will be done from water surface of the Paulo Gorsk Municipal Lake in Cascavel-PR. The methods procedures used by the laboratory are analytical based on Standart methods for the examination of water and wastewater, American Public Health Association (APHA), American Water Works Association (AWWA) e Water Environment Federation (WEF). The results of the laboratorial analysesshow a good porcentage in realation to thalesaapolute substances Iron (Fe) in until 93,73% and Zinc (Zn) in 97,38%.Thus, the benefits environmental contributions that contribute significantly, not only to mitigate the various effects resulting from the urbanization process, but as a strategy to ensure environmental quality in urban spaces. With this work it can realize that the, the environmental cbenefits are good, not only to mitigate of the various effects resulting from the urbanization process, but as strategy to ensure environmental quality in urban spaces.